Pelatihan Penerapan Motif Tradisi Jawa pada Pengrajin Asesoris di Prapen Jewelry Denpasar - Yuniana Cahyaningrum; Rahayu Adi Prabowo; Arfiati Nurul Komariah; Cerly Sudarta Martsidaun; Sutriyanto; Satria Bagus Wibowo (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2024)
This training aims to improve the understanding and skills of accessory craftsmen at Prapen Jewelry, Denpasar, in applying traditional Javanese motifs to their products. Traditional Javanese motifs have high aesthetic value and are full of cultural philosophy that can enrich the appeal of contemporary accessories. The training method includes a theory session to introduce the history and meaning of Javanese motifs, as well as hands-on practice to integrate these motifs into product design. The results of the training showed an increase in creativity and innovation of craftsmen in developing products that combine traditional and modern elements. This training also opens up wider market opportunities for accessory products with a touch of local culture. Thus, the application of traditional Javanese motifs not only preserves cultural heritage but also provides added economic value for craftsmen